PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL PEMODERASI - YUNIASIH, NI WAYAN; WIRAKUSUMA, MADE GEDE (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 1 (2009), 2009)
Researches on the influence of financial performance on corporate value have been widely conducted, however results inconsistency occurred. Financial performance, which in this case is assessed by Return on Assets (ROA), have a positive effect on corporate value, however there are also some findings that ROA have a negative effect. Researchers predicted that there are other influencing factors. This condition drives researchers to use corporate social responsibility (CSR) and good corporate governance (GCG) as moderating variables. This research aims to test the influence of financial performance on corporate value by considering the two moderating variables. This research uses 27 manufacturing firms listed on the Jakarta Stock Exchange during 2005 - 2006 as samples with 54 observation Hypothesis is tested using moderated regression analysis to find out the interactive influence of the moderating variables. The corporate value measured using Tobin's Q, while disclosure of CSR and GCG are measured with CSR Index and managerial ownerships, respectively.. Results indicate that (1) ROA has a positive effect on corporate value, (2) the disclosure of CSR is able to moderate relation of ROA and corporate value, but managerial ownerships are unable to moderate the link. This is possible because managerial ownerships in Indonesia is still very small and companies tend to be family-owned.
Keywords: financial performance, corporate value, CSR disclosure, good corporate governance